The Uses of Free Time in Black Couples Residing in Cali - Orobio, César Augusto (Sociedad y Economía, 2024)
The objective of this article is to analyze the changes in the use of free time among Afro-descendant married couples residing in Cali. A survey of seventeen couples in the city was conducted, complemented by interviews. The study reveals how the use of free time varies among these couples, ranging from shared activities to segregated ways of enjoying leisure. It suggests that this change can be explained by the transition from romantic love ideals to care-related forms of love established within the marital relationship.